Risk regulation at risk : restoring a pragmatic approach - Shapiro, Sidney A., 1947- (Stanford University Press, 2003)
"In this book, the authors propose that the American tradition of philosophical pragmatism fills this vacuum. They argue that pragmatism offers a better method for conceiving of and implementing risk regulation than the economic paradigm favored by its critics. While pragmatism offers a methodology in support of risk regulation as it was originally conceived, it also offers a perspective from which this legislation can be held up to critical appraisal. The authors employ pragmatism to support risk regulation, but pragmatism also leads them to agree with some of the criticisms against it and even to level new criticisms of their own."